NASA: Influence of a strong organizational culture - Linstead, Stephen (Henry Stewart Talks, 2018)
This case study scrutinises NASA's organisational culture during the Challenger disaster of 1986 and the Columbia disaster of 2003. At NASA, past successes created an environment of overconfidence and organisational structures prevented safety concerns reaching the top-decision makers. The combination of these factors provided a cultural environment conducive to disaster.